THE EFFECT OF VITAMIN C ON LUNG FUNCTION AFTER CARDIAC SURGERY. - Karadzic Kocica, Milica; Markovic, Dejan; Ristic, Arsen (Medicinski podmladak, 2024)
The systemic inflammatory response is an integral part of any cardiac surgery during which an out-of-body blood stream machine is used. During the operation, the blood is exposed to a foreign body belonging to the tubes themselves, which are part of the extracorporeal bloodstream and this is the reason why inflammation, increased production of free radicals, coagulopathy and organic dysfunction after cardiac surgery occurs. Vitamin C as a potent antioxidant vitamin has been used in cardiac surgery in recent years as well as in other surgery precisely because of its antioxidant properties. It also affects coagulation and can prevent dysfunction of many organs. In this paper, we will look at the role of vitamin C when it comes to lung function after cardiac surgery.